Analisis Normatif Putusan Hakim tentang Pemberian Iddah dan Mut’ah sebelum Ikrar Talak - Itsna Faiqatul Himmah; Endrik Safudin; Putri Oktafiani; Rahmawati Laila Alfia (Jurnal Antologi Hukum, 2022)
The consequences of breaking up a marriage are regulated in the Compilation of Islamic Law (KHI) Chapter XVII Article 149 Compilation of Islamic Law, post-divorce maintenance is carried out after the pronouncement of the divorce vow, what is meant by the breakup of the marriage is after the divorce has occurred, in which divorce is considered valid if the arrangement for the divorce pledge is carried out in front of the judges. The provision of Iddah and Mut'ah in the Compilation of Islamic Law and Legislation is not explained precisely when it should be given. Still, in the Decision of the Ponorogo Religious Court Number 1978/Pdt.G/2021/Pa.po, its ruling states that providing iddah and mutah Mut'ah is given to the wife before pronouncing the divorce vow. This study aims to answer questions (a) What is the legal basis for the judges of the Ponorogo Religious Court in deciding Case Number 1978/Pdt.G/2021/Pa.po concerning the provision of iddah and mut'ah maintenance before pronouncing the divorce pledge? (b) What is the juridical implicit of the provision of iddah and mut'ah maintenance before the pronouncement of the divorce pledge in Case Decision Number 1978/Pdt.G/2021/Pa.po at the Ponorogo Religious Court? This field research using a qualitative approach shows that (a) in deciding case Number 1978/Pdt.G/2021/Pa.po the judge prioritized PERMA Number 3 of 2017, because it is more responsive to women and can protect women's rights post-divorce (b) The Juridical Implications of Decision Number 1978/Pdt.g/2021/Pa.po is by the Compilation of Islamic Law Article 131 letter c, the Petitioner is given a deadline of 6 months and if the Applicant is unable to fulfill the iddah and mut'ah maintenance payments, then the implementation of the pronouncement of the divorce vow cannot be carried out (aborted), the Petitioner and the Respondent will remain legally husband and wife because they are considered not serious about carrying out a divorce. Akibat dari putusnya perkawinan diatur dalam Kompilasi Hukum Islam (KHI) Bab XVII Pasal 149 Kompilasi Hukum Islam, pemberian nafkah pasca perceraian dilakukan setelah pengucapan ikrar talak, yang dimaksud putusnya perkawinan adalah setelah terjadinya perceraian, yang mana perceraian dianggap sah apabila pengucapan ikrar talak dilakukan di depan majelis hakim. Pemberian nafkah Iddah dan Mut’ah dalam Kompilasi Hukum Islam dan Peraturan Perundangan tidak dijelaskan secara pasti kapan seharusnya diberikan, namun dalam Putusan Pengadilan Agama Ponorogo Nomor 1978/Pdt.G/2021/Pa.po dalam amarnya menyatakan bahwa pemberian nafkah iddah dan mut’ah diberikan kepada isteri sebelum pengucapan ikrar talak. Penelitian ini bertujuan untuk menjawab pertanyaan (a) Bagaimana dasar pertimbangan hukum Hakim Pengadilan Agama Ponorogo dalam memutuskan Perkara Nomor 1978/Pdt.G/2021/Pa.po tentang pemberian nafkah iddah dan mut’ah sebelum pengucapan ikrar talak? (b) Bagaimana implikasi yuridis terhadap pemberian nafkah iddah dan mut’ah sebelum pengucapan ikrar talak pada Putusan Perkara Nomor 1978/Pdt.G/2021/Pa.po di Pengadilan Agama Ponorogo?. Penelitian lapangan dengan pendekatan kualitatif ini menunjukkan bahwa (a) dalam memutus perkara Nomor 1978/Pdt.G/2021/Pa.po hakim mengutamakan PERMA Nomor 3 Tahun 2017, karena lebih responsif terhadap perempuan, dan dapat melindungi hak-hak perempuan pasca perceraian, (b) Implikasi Yuridis dari Putusan Nomor 1978/Pdt.g/2021/Pa.po ini sesuai dengan Kompilasi Hukum Islam Pasal 131 huruf c, Pemohon diberi tenggat waktu 6 bulan dan apabila Pemohon tidak bisa memenuhi pembayaran nafkah iddah dan mut’ah, maka pelaksanaan pengucapan ikrar talak tidak dapat dilaksanakan (gugur), Pemohon dan Termohon akan tetap menjadi suami isteri yang sah, karena dianggap tidak serius untuk melaksanakan perceraian